Conversion of Oil Palm Kernel Shell Biomass to Activated Carbon for Supercapacitor Electrode Application - Izan Izwan, Misnon; Nurul Khairiyyah, Mohd Zain; Rajan, Jose (Springer, 2018)
Electrochemical charge storage of physically and chemically activated carbon synthesized from oil palm kernel shell (PKS) in three different aqueous electrolytes (1 M H2SO4, 1 M Na2SO4 and 6 M KOH) are presented. Coin type CR2032 cells fabricated using the PKS ACs electrodes separated by fiber glass separator and electrolyte are used as devices for measurements. Achievable operating potential for these devices varied as H2SO4 (1.0 V) < KOH (1.2 V) < Na2SO4 (2.0 V). The highest energy density was obtained in Na2SO4 electrolyte (7.4 Wh kg−1) at a power density of 300 W kg−1. The device stability cycle at low current density (0.5 A g−1) for 3500 times showed capacitance retention in range of 78–114% in all devices.